Penggunaan Metode Single Moving Average (SMA) Untuk Meramalkan Kasus Kecelakaan Lalu Lintas di Kota Blitar - Sanwidi, Ardhi (Universitas Nahdlatul Ulama Blitar, 2025)
Traffic is a subsystem of the urban ecosystem, developing as a part of the city due to the instincts and needs of the population to move or use transport to move people and or goods from somewhere else. Blitar City is one of the cities in eastern Java with 32.58 km2 and 3 districts such as Sukorejo, Kepanjenkidul, Sananwetan. In this study we discussed a case of civil accidents under the jurisdiction of the Blitar City Police Resort. The study aims to predict and analyze the case of an accident in Blitar City in January 2024. The investigation will take place in January 2024 at the Blitar City Police Resort.The method used in this investigation is the Single Moving Average (SMA). Historical data on the number of accidents in each period is used to implement predictions using the method (SMA). The initial stage is carried out by analyzing actual data that is then applied in the method, to obtain predictive data using the parameter . The results of this study show that the SMA method can be well used to predict the number of acceptable accidents. Obtained calculations for January of 35 accidents, with MSE error values of 54,79348 and 1,543478 for MAD values. Based on the research results, it can be seen that the number of accidents in Blitar City is decreasing.